PROSES PENEMPATAN PEGAWAI NEGERI SIPIL DI DINAS PERKEBUNAN PROVINSI KALIMANTAN BARAT - Hakim E.01108006, Arwin Amru (FISIP Universitas Tanjungpura, 2013)
The title of this article is cent Placement Civil Servants In the Plantation Office of West Kalimantan Province. The article was based on the placement error Plantation Office of the Civil Service of West Kalimantan Province in General and Administrative Section, An error in the placement of the Civil Service Office of West Kalimantan Plantation In Marketing Section. From both these problems, will greatly affect the activity and human resource management activities in particular in achieving organizational goals or government. This in turn will affect the human resource management employee less than optimal. The formulation of the problem is presented in order to clarify the objectives contained in this research, in particular that this study does not deviate from the predetermined target more, especially in collecting data in the field. Thus the formulation of this problem is: